El positivismo: primer esfuerzo por crear una ciencia de la sociedad. - Salazar Zapatero, Hector (2007)
This ('.1'.\'(,/," (d/á, a tlteoretical contributionfor uuderstand the origin aud the structure (!{ positivism as a current ofphil()s()"/~I: Allholl~/¡ posiuvism II'(/.\' ouc oftbc I/WSI influcnt philosophical curren! in natural and social sciences during the l.'//Oleninetieth and {I! the hegilll1;ngvi the IHC'lIlielhcentury maintains its importance until our days. especialtv in investigation arca, JI;.\' erector y principal representative 'HIS Isidoro :111}.;'1I.\1O Maria Javier Conue.Llis illlagina/ioll cfsocietv rcspondsto lile nccessity ofthe, '01I1//? hOlIl~(,t)isie established as a nn\' socia! class ,!fier the trench Rcvoluuon. who 11',/,1 ioukil/g /¡)r a correa kl/OldedKt'concomed wiilt societv. 10 be abl« lo (.'O/lSI/'UCl (/ 1/"11 ,IIIL¡,JI .\Y.\¡I '111 which refleas their interests.Pos¡';il'islIIl/¡illki.'lg \','{I.I il/I/II(.'//ce;,/ bvt« 'O ill/p(J/'íiI//! incident»: 011 one hand Il'ilS th« Il'~'II)I'(¡li()1I,..hiel: tmplied tlu: IJ/US!CUI!.\('}'\'illi',v ,~'intcn¡« 10 reestoblish the Ieudu! S\'~/('/}/ uuificd in th« JI!)/r Allianc«. O» ,'/1<' ',I(/n',..luuu! ",','r,' tiu: people who \I'L~/'(;' disaccording with thc achicvcmcru», iiJl' ¡!¡:/! {/¡el i/!ic'II,ÍI'I/ to cotniuuc with tlte changes. These circumstauccs ,..ere !'t's{'()l!s¡hit'bccuu.«: !'t)"ill"'¡~/II «il! he' injluell(,(~ (he constttutton ofsocial science. hUI ulso are dctcrmined ti' 11/1 id('oiogy